The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00438-017-1363-8
|View full text |Cite
|
Sign up to set email alerts
|

Dispersals of the Siberian Y-chromosome haplogroup Q in Eurasia

Abstract: The human Y-chromosome has proven to be a powerful tool for tracing the paternal history of human populations and genealogical ancestors. The human Y-chromosome haplogroup Q is the most frequent haplogroup in the Americas. Previous studies have traced the origin of haplogroup Q to the region around Central Asia and Southern Siberia. Although the diversity of haplogroup Q in the Americas has been studied in detail, investigations on the diffusion of haplogroup Q in Eurasia and Africa are still limited. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 84 publications
2
19
0
Order By: Relevance
“…Both tools indicated that this individual belonged to the y-Haplogroup Q1a2b2 (Q-L933). The Q haplogroup was found to have originated in Central Asia and Southern Siberia, subsequently migrating toward Eurasia, and arriving in the Arabian Peninsula 3537 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both tools indicated that this individual belonged to the y-Haplogroup Q1a2b2 (Q-L933). The Q haplogroup was found to have originated in Central Asia and Southern Siberia, subsequently migrating toward Eurasia, and arriving in the Arabian Peninsula 3537 .…”
Section: Resultsmentioning
confidence: 99%
“…However, a study of 471 individuals with subclades of the Q haplogroup by Huang et al . (2018) concluded that the Q haplogroup originated from Central Asia and Southern Siberia and dispersed to the Amerind and subsequently to whole Eurasia and part of Africa 37 . The Q haplogroup was found to have arrived in the Arab Gulf region, across Iran, from central Southern and Southeast Asia and were found to be abundant in the UAE, Iran and Pakistan 36 .…”
Section: Discussionmentioning
confidence: 99%
“…TMRCA calculated for R1a individuals from different regions of India was comparable to TMRCA of R1a individuals of GJ populations. Haplogroup Q is believed to have originated in Central Asia and southern Siberia region around 15-25 kya 24,25 , followed by its spread elsewhere in the world. The TMRCA of 11 kya for haplogroup Q individuals in the Ladakh region point to a possible migration from the region of origin to Ladakh.…”
Section: Discussionmentioning
confidence: 99%
“…A number of Q1-M242 samples have also been found in ancient remains from South Siberia and adjacent regions [56,57]. Other sub-lineages of Q-M242 are scattered widely in different geographic regions of Eurasia, including Q1-L275, Q1-M25, and Q1-Y2659 [14,35,37,58]. Additionally, the Y-chromosome of a 6000-5100 BCE sample (I4550) from Zvejnieki, Latvia has been identified as Q1-L56 [59].…”
Section: Differentiation and Diffusion In Paleolithic Siberiamentioning
confidence: 99%
“…Furthermore, ancient DNA studies have shown that the~12.6-ky-old Anzick-1 boy belongs to the Q1-FGC47532 sublineage of haplogroup Q1-Z780 [8]. However, few works have mentioned haplogroup Q-L804 [37] and Q-Z780 [14]. Previous studies focused on the internal diversity of paternal gene pool of American aborigines and little is known about the differentiation process of founding paternal lineages of American aborigines from their close relatives in Siberia and more broadly in Eurasia.…”
Section: Introductionmentioning
confidence: 99%